Learning by Playing: Echo and Tact in Expanding the Verbal Repertoire of Infants - Thaise Löhr; Maria Stella Coutinho de Alcantara Gil (Paidéia (Ribeirão Preto), 2015)
To refer to an object or event by providing its corresponding name is an important acquisition in the learning of verbal behavior. The relationship between the spoken name and its referent, called tact, is considered essential in the expansion of verbal repertoires in children. This study aimed to teach tact to four institutionalized children, aged between 26 and 29 months, with reduced exposure to verbal stimulation. The procedure introduced playful characteristics into the teaching of tact and the required repertoire, which was the emission of echoic responses, through procedures typically used to teach verbal repertoire for children with language delay. All children learned to tact (and echo). The procedure was effective in increasing the echoic repertoire and promoting the acquisition of the tact repertoire. These results confirm the literature that considers learning echoic repertoire to be a requirement for the acquisition of tact.